Functional performance of 8 small surgical aortic valve bioprostheses: an in vitro study. (22nd August 2022) - Sadat, Najla; Scharfschwerdt, Michael; Schaller, Tim; Aboud, Anas; Saisho, Hiroyuki; Ensminger, Stephan; Fujita, Buntaro
Abstract: OBJECTIVES: Selection of a surgical aortic valve (SAV) bioprosthesis model for the treatment of aortic valve disease remains controversial. The aim of this study was to characterize the functional performance of 8 SAV models in a standardized in vitro setting. METHODS: The hydrodynamic performance of 8 SAVs with labelled size 21 mm (Avalus™, Hancock ® II, Mosaic ® Ultra™, Perimount ®, Perimount ® Magna Ease, Epic™ Supra, Trifecta™ GT; Freestyle ® ), was investigated in a pulse duplicator. Transvalvular pressure gradients and effective orifice area (EOA) were recorded. The geometrical orifice area and physical dimensions of the valves were determined, and new functional dimensions were introduced. RESULTS: Mean pressure gradient (MPG) and EOA differed significantly between the analysed SAVs. The Epic presented with the lowest EOA and highest MPG, while the Trifecta showed the highest EOA and the lowest MPG. We introduce a useful way to determine the minimal internal diameter and a new measure termed 'relative orifice area' to characterize a valve's performance. CONCLUSIONS: SAVs showed significant differences in their hydrodynamic performance despite the same label size. This finding was related to the construction of the valves. We introduce a new measure that characterizes the functional performance of a valve model and size for the treatment of an aortic annulus of a specific size. Our data emphasize that SAV selection should carefully be done using an individual patient approach and that future research is necessary to improve the current generation of SAVs. Abstract : According to the implantation technique, aortic valve bioprostheses are classified into surgical aortic valve (SAV) bioprostheses, including conventional and rapid deployment (also known as sutureless) prostheses, and transcatheter heart valves [1].